Exploring textual meaning-making in Indonesian EFL learners’ writing: A systemic functional perspective - Lutfiyana, Faza; Kurniawan, Eri (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
Drawing on the framework of theme systems in systemic functional linguistics, this study aimed to explore the students writing in textual meaning-making. The explanation text was the genre of the sample. The students wrote about different topics. Then, the researcher focused on content, organization, vocabulary, and grammar. The data were collected from 3 secondary students’ writing tasks in Temanggung, central Java. Functional text analysis was used to analyze the data including, the Ideational, interpersonal, and textual themes system. The results represent that the students exaggerate the use of certain types of theme systems. for example, in the case of the topical theme. The analysis accounted that several students use this way but ignore the others. Most nominal groups appear in the clause and have fewer modalities. The textual theme is dominant in this paper and ideational (for instancehe use of conjunctive and continuative) is median, and the Interpersonal theme (modality) is the lowest. In summary, introducing the modality systematically and providing more contexts for learners to practice it is highly recommended in such a context.